Les Déterminants Idiosyncratiques De La Performance Bancaire Au Maroc : Analyse Sur Données De Panel - Salwa Bahyaoui (European Scientific Journal, ESJ, 2017)
If the financial crisis of 2008 raised the interest in analyzing the impact of the financial system, particularly the banking one, on the real economy ; studies were focused on macroeconomic variables given the crisis fallout. However, in spite of its propagation to the international scale, the financial crisis has impacted more severely some developed economies. Rightly, the Moroccan banking system was slightly affected. This suggests a specificity of the Moroccan context. The aim of this study is, therefore, to apprehend the banking performance in Morocco from a microeconomic point of view. To do so, a panel data analysis relative to eight banks was conducted over the period 2004-2015. The results allowed to identify the determinants of banking performance in the Moroccan context while confirming certain specificities of the banking system in Morocco.